Functional traits of broad-leaved monocot herbs in the understory and forest edges of a Costa Rican rainforest - Rundel,Philip W.; Cooley,Arielle M.; Gerst,Katharine L.; Riordan,Erin C.; Sharifi,M. Rasoul; Sun,Jennifer W.; Tower,J. Alexandra (PeerJ, 2020)
Broad-leaved monocot herbs are widespread and dominant components of the shaded understories of wet neotropical forests. These understory habitats are characterized by light limitation and a constant threat of falling branches. Many shaded understory herb species have close relatives that occupy forest edges and gaps, where light availability is higher and defoliation threat is lower, creating an opportunity for comparative analysis of functional traits in order to better understand the evolutionary adaptations associated with this habitat transition. We documented ecological, morphological and ecophysiological traits of multiple herb species in six monocot families from each of these two habitats in the wet tropical rainforest at the La Selva Biological Station, Costa Rica. We found that a mixture of phylogenetic canalization and ecological selection for specific habitats helped explain patterns of functional traits. Understory herbs were significantly shorter and had smaller leaves than forest edge species. Although the mean number of leaves per plant and specific leaf area did not differ between the two groups, the larger leaf size of forest edge species gave them more than three times the mean plant leaf area. Measures of leaf water content and nitrogen content varied within both groups and mean values were not significantly different. Despite the high leaf nitrogen contents, the maximum photosynthetic rates of understory herbs were quite low. Measures of δ13C as an analog of water use efficiency found significantly lower (more negative) values in understory herbs compared to forest edge species. Clonality was strongly developed in several species but did not show strong phylogenetic patterns. This study highlights many functional traits that differ between broad-leaved monocot species characteristic of understory and forest edge habitats, as well as traits that vary primarily by phylogenetic relatedness. Overall, plant functional traits do not provide a simple explanation for the relative differences in abundance for individual understory and forest edge species with some occurring in great abundance while others are relatively rare.
Keywords: Understory; Forest edge; Tropical forest; Araceae; Costaceae; Marantaceae; Zingiberaceae; Cyclanthaceae